The validity of numbered heads strategy test and its relationship to learning some rhythmic gymnastics skills for female students at the College of Physical Education and Sports Sciences (Texas Journal of Multidisciplinary Studies, 2025)
The researcher used a correlational approach with the descriptive method. One hundred female students from Tikrit University's College of Physical Education and Sports Sciences for the 2023–2024 academic year made up the research population. The sample, which included fifty second-year students, was purposefully chosen. The numbered heads strategy exam was used by the researcher to acquire rhythmic gymnastics skills. After dividing the sample into two groups and gathering data, the researcher employed statistical tools via the Statistical Package for Social Sciences (SPSS) to provide findings that supported the study's goals